Analisis Deskriptif Penyebab Kekerasan Dalam Rumah Tangga Terhadap Perempuan - Miftahul Jannah; Moh. Amin Tohari (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research discusses the causes of domestic violence (KDRT) against women. The aim of this research is to find out the impact of the causes of domestic violence that occur in RT 003 RW 011 Pondok Pinang. This research is qualitative research in collecting data using observation, interviews and documentation methods. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Triangulation is used to explain the validity of the data obtained. The findings of this research show what women go through in terms of social function from the physical and mental levels they have gone through. The results of the research reveal that the causes of domestic violence against women occur due to economic difficulties, excessive emotions and disobedience, while several impacts are experienced by the victim, such as psychological impacts such as post-traumatic stress, shame and anxiety for the partner, first. both physical impacts such as bruises and bruises.